CT-guided radiofrequency ablation in osteoid osteoma: Result from a tertiary cancer centre in India - Kulkarni, Suyash S; Shetty, Nitin S; Polnaya, Ashwin M; Janu, Amit; Kumar, Suresh; Puri, Ajay; Gulia, Ashish; Rangarajan, Venkatesh (Indian Journal of Radiology and Imaging, 2017)
Aims: The aim of this study is to evaluate the clinical efficacy of computed tomography (CT)-guided radiofrequency (RF) ablation as a minimally invasive therapy for osteoid osteoma. Materials and Methods: This is a retrospective analysis of prospectively maintained data of 43 symptomatic osteoid osteoma patients who were treated by radiofrequency ablation (RFA). Forty out of 43 patients were naive cases and underwent primary treatment for osteoid osteoma with RFA, whereas 3 patients included in the study underwent RFA for local recurrence after having undergone surgical treatment. Diagnosis was based on clinical and characteristic imaging findings, and biopsy was done for cases with atypical presentation. Pre and post procedure Visual Analog Score (VAS) was documented in all cases. Monopolar RFA system was used in all patients, and the electrode was placed within the lesion nidus under CT guidance coaxially through 11G introducer needle. Ablation was performed at 90° C for 5 min. Results: Technical success rate of intranidal placement of electrode was 100%. The primary clinical success in our study was 97.7% (42 of 43), and the secondary clinical success was 100%.Pre and postprocedure VAS score in our study group was 7.8 and 0.4, respectively. Mean follow-up period in our study was 48 months (Range: 4–129 months).One patient had recurrence of pain 4 years after treatment and was treated successfully by a second session. Minor complications were seen in 3 patients with two cases of RF pad burns and one case of skin burn at the treatment site, and these were managed conservatively. No patients developed temporary/permanent neurological deficits, and no procedure-related mortality was seen in our study. Conclusion: CT-guided percutaneous RFA is a simple, safe, minimally invasive, and highly effective treatment option for osteoid osteoma with good long-term pain control and potentially low disease recurrence.
Keywords: Bone ablation; bone RFA; osteoid osteoma; PET-CT; radio frequency ablation